2012
DOI: 10.5713/ajas.2011.11462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cattle Breed on Meat Quality, Muscle Fiber Characteristics, Lipid Oxidation and Fatty Acids in China

Abstract: The objective was to compare meat quality, muscle fiber characteristics, lipid oxidation and fatty acids of Limousin (LIM), Simmtental (SIM), Luxi (LX), Qinchuan (QC) and Jinnan (JN) offered the same diet in China. After finishing, eight bulls from each breed were randomly selected for slaughter at 18.5 months old. Longissimus dorsi (ld) muscle was taken from the carcass for meat quality evaluations. Breed had little effect on most of meat and fat color parameters except for Hue and b* in which QC had lower va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
39
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 30 publications
12
39
0
4
Order By: Relevance
“…Therefore, it is necessary to closely monitor the health of animals, since only a healthy body has the ability "to balance itself" in this environment, to resist it, to adapt to the new mode of life [5][6][7][8] . To date, the state and adaptation of these animals to new climatic conditions are quite good; therefore it is necessary to develop the technology for the better adaptation of animals to the conditions of Nrthern Kazakhstan.…”
mentioning
confidence: 99%
“…Therefore, it is necessary to closely monitor the health of animals, since only a healthy body has the ability "to balance itself" in this environment, to resist it, to adapt to the new mode of life [5][6][7][8] . To date, the state and adaptation of these animals to new climatic conditions are quite good; therefore it is necessary to develop the technology for the better adaptation of animals to the conditions of Nrthern Kazakhstan.…”
mentioning
confidence: 99%
“…Beef showed the lowest intensity of yellowness (b*), which could be due to the highest content of intramuscular fat and the highest degree of lipid oxidation. Xie et al (2012), who compared meat colour parameters in different breeds, found that they did not differ in L* and a* values. These parameters were similar to ours but there were differences in b* value.…”
Section: Intrinsic Properties Of the Meatmentioning
confidence: 97%
“…In their study, Xie, Meng, Cui, and Ren (2012) determined meat pH, subcutaneous fat and muscle color, texture, chemical composition, lipid oxidation and fatty acid composition, in the longissimus dorsi. Among the imported breeds, Limousin had a proven advantage over Simmental with regard to meat quality.…”
Section: Meat Quality Of Indigenous Cattle Breedsmentioning
confidence: 99%